Comparative Characteristics of Professional Accounting Judgments Classification Features - E. V. Zimina; O. A. Frolova (Учёт. Анализ. Аудит, 2020)
The article is devoted to the problem of forming a unified conceptual model for the application of professional accounting judgment. The model takes into account not only the concept, but also the prerequisites, conditions of application and the process of judgment developing along with non-standard situations on which an accountant can express his competent opinion. The methodological framework of the study is based on the scientific developments of domestic and foreign scientists regarding the classification of professional accounting judgments and their comparative characteristics. The research methodology provides for the systematization of types of accounting judgments that affect the financial and economic activities of the organization. The result of the research is the development and justification of the author’s classification of accounting judgments singling out such classification features as organizational and legal form of a business, type and scope of economic activity, financial condition and accounting standards applied, which makes it possible to determine the purpose of professional judgment of an accountant. The further specification of classes and the development of classification features of professional accounting judgment will result in perceiving this category not only as a tool for solving applied accounting problems, but also as a conceptual platform built into the structure of accounting theory. The proposals based on the study are intended for effective use of accounting judgments as a comparatively new accounting and reporting tool to generate accounting and analytical information by the specialists of accounting departments of different organizations. The system of classification decisions will most fully define the role and designation of accounting judgments in accounting practice.